Palliative sedation: not just normal medical practice. Ethical reflections on the Royal Dutch Medical Association's guideline on palliative sedation - Janssens, Rien (Journal of medical ethics, 2012)
The main premise of the Royal Dutch Medical Association's (RDMA) guideline on palliative sedation is that palliative sedation, contrary to euthanasia, is normal medical practice. Although we do not deny the ethical distinctions between euthanasia and palliative sedation, we will critically analyse the guideline's argumentation strategy with which euthanasia is demarcated from palliative sedation. First, we will analyse the guideline's main premise, which entails that palliative sedation is normal medical treatment. After this, we will critically discuss three crucial propositions of the guideline that are used to support this premise: (1) the patient's life expectancy should not exceed 2 weeks; (2) the aim of the physician should be to relieve suffering and (3) expert consultation is optional. We will conclude that, if inherent problematic aspects of palliative sedation are taken seriously, palliative sedation is less normal than it is now depicted in the guideline.